A Novel Approach for Human Identification using Sclera Recognition - Rajan, Gokul Rajan V; Vijayalakshmi, S (International Journal of Computer Sciences and Engineering, 2025)
Securing data in today’s computing environment is an important aspect. Biometrics is one of the techniques which provide reliable security on the data in this insecure world. Currently, iris, face, finger print, palm have been employed in biometric authentication to authorize the person. Due to its unique behavior, biometric systems provide a good reliable and prominent environment. In recent research on biometric authenticity, it is proved that the vessel patterns of sclera are unique and it is applicable throughout the human lifetime. The sclera recognition consists of various stages, among which sclera segmentation and the feature extraction are the important stages as they decide the accuracy of the system. Feature extraction is to be done after segmentation and enhancement of the vessel patterns. This paper discusses proposal of robust method using canny based segmentation and Harris corner feature extraction techniques